Structural, electronic, optical, and mechanical properties of the all-inorganic lead-free metal halides double perovskites Cs2RbInX6 (X = Cl, Br, I): A first-principles based study - Luo, Muxuan; Luo, Jiaolian; Dong, Jialiang; Yang, Anqi; Xie, Zhenyu (Materials science & engineering. B, Solid-state materials for advanced technology, 2023)
•The first principles study of the little-studied Cs2RbInX6 (X = Cl, Br, I)•Cs2RbInX6 (X = Cl, Br, I) is a direct band gap compound.•Halogen replacement significantly improves optical properties.•The compound meets the mechanical stability.•A promising material for ultraviolet detectors. Lead-free metal halides double perovskite is an ideal alternative to lead-based perovskite and is poised to shine in the field of optoelectronics as a new and emerging photoelectric material. In this paper, we take as a starting point the halide double perovskite Cs2NaInCl6 which is a subject with well-established research results and determined the little-studied structure Cs2RbInCl6 by the replacement of the same-group element, and explore the effects of halogen substitution on the different properties, computational experiments and analyses of the Cs2RbInX6 (X = Cl, Br, I) have been carried out. Depending on the First-Principles studies, the band structure, density of states, optical and mechanical properties of this compound have all been systematically explored. The Materials Studio package's Castep code was used for all computational experiments. The tolerance factor (τ) reveal that Cs2RbInI6 is less stable than Cs2RbInCl6 and Cs2RbInBr6. The band gaps of all three compounds are direct. The light absorption is mainly attributed to the transition from the halogen X-p orbital to the In-s orbital. While Cs2RbInCl6 and Cs2RbInBr6 have no absorption occurring in the visible and infrared regions and possess a wide band gap, which considers them promising candidates for use in the ultraviolet detector. The replacement of halogen has noticeably enhanced the optical properties. The Cs2RbInX6 (X = Cl, Br, I) also meets the requirements for mechanical stability and is ductile, anisotropic, and toughness. Sequentially decreasing band gap values when the halogen from Cl to I, also obviously affects the placements of the threshold points and peaks in the various spectral figures and the macroscopic mechanical properties. The work presented in this paper sheds light on the electronic, optical, and mechanical characteristics of Cs2RbInX6 (X = Cl, Br, I), offering corresponding theoretical support for the related experimental research and promoting the possibility for the development of novel optoelectronic devices.